The Protection of Human Rights in the Case of Non-Criminal Narcotics Users - Laksana, Andri Winjaya (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Narcotics use as a complex global issue has an impact on human rights, especially in the context of criminal law. Although some countries, including Indonesia, are beginning to recognize human rights protections in non-criminal narcotics use, the main challenge is striking a balance between strict regulation and appropriate protection for individuals who need narcotics for treatment or non-criminal purposes. Purposes of the Research: The aim of this research is to analyze relevant laws and regulations and related practices in protecting human rights in the case of non-criminal narcotics users. Methods of the Research: This research uses normative legal research methods to analyze laws and regulations related to non-criminal narcotics use. Data sources include statutory documents, court decisions, and legal literature. Data analysis will look for patterns and evaluate regulatory compliance with human rights principles.Results of the Research: To protect human rights in cases of non-criminal narcotics use in Indonesia, legislation plays an important role, although challenges such as abuse of power and social stigma remain. Cooperation between government, NGOs and civil society is needed to implement existing regulations and increase public understanding of human rights. Indonesia needs to find a balance between strict narcotics regulations and protecting individual rights. This involves clear definitions for “non-criminal” narcotics, fair law enforcement, as well as safeguarding individual privacy. The challenges involve racial and social injustice in drug law enforcement and require an evidence-based approach that engages diverse stakeholders. Continuous research and analysis is needed to support better policies to address the narcotics problem.